2012
DOI: 10.1177/2158244012448487
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change as a Wicked Problem

Abstract: Understanding complexity suggests that some problems are more complex than others and defy conventional solutions. These wicked problems will not be solved by the same tools and processes that are complicit in creating them. Neither will they be resolved by approaches short on explicating the complex interconnections of the multiple causes, consequences, and cross-scale actors of the problem. Climate change is one such wicked problem confronting water management in Ghana with a dilemma. The physical consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Peters, 2017). A large number of studies have identified highly wicked or complex (environmental) problems, which are prone to failure (Cilliers et al, 2013;FritzGibbon & Mensah, 2012;Huntjens et al, 2012;Jentoft & Chuenpagdee, 2009;Metz & Ingold, 2014;Pahl-Wostl, Lebel, Knieper, & Nikitina, 2012;Patterson, Smith, & Bellamy, 2013). Many researchers analyse the effects of single dimensions of wickedness such as linear dynamics on solutions but do not combine various dimensions in one study design (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Peters, 2017). A large number of studies have identified highly wicked or complex (environmental) problems, which are prone to failure (Cilliers et al, 2013;FritzGibbon & Mensah, 2012;Huntjens et al, 2012;Jentoft & Chuenpagdee, 2009;Metz & Ingold, 2014;Pahl-Wostl, Lebel, Knieper, & Nikitina, 2012;Patterson, Smith, & Bellamy, 2013). Many researchers analyse the effects of single dimensions of wickedness such as linear dynamics on solutions but do not combine various dimensions in one study design (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ghana is among countries where climate change is being experienced through the rise in temperatures and unpredictable rainfall across all ecological zones [6]. As far as water resources management and use are concerned, three climate change affiliated issues are relevant: extreme events brought about by changes in sea-level rise and variability, temperature regimes and rainfall [7]. Climate change remains an issue for the whole country, but climate variability is a major challenge, especially for rural areas that depend on natural resources and environmental factors/practices [8].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change remains an issue for the whole country, but climate variability is a major challenge, especially for rural areas that depend on natural resources and environmental factors/practices [8]. For rural indigenes without piped water, irregularity and severe in weather patterns (droughts and floods) instantly influence water availability and access, placing additional stresses on their daily activities [7]. According to [8] there is no doubt that the climate in Ghana has changed significantly with impacts being felt in every part of the country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no easy solutions to Wicked Problems, and though enormous progress can be made in alleviating them, they will remain with us. As John Fitzgibbon and Kenneth O. Mensah point out in Climate Change as a Wicked Problem, there is a "deficiency in our technical and social capabilities to be able to deal with a phenomenon with multiple sources, actors, stakeholders, cross-scale influences (externalities), and linkages" (Fitzgibbon & Mensah, 2012).…”
Section: Now Goldman Sachs) Mcknight and Mellonmentioning
confidence: 99%